2016
DOI: 10.1002/chem.201601836
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Driven Scaffold Diversity: Selective Synthesis of Spirocycles, Carbazoles and Quinolines from Indolyl Ynones

Abstract: Medicinally relevant spirocyclic indolenines, carbazoles and quinolines can each be directly synthesised selectively from common indolyl ynone starting materials by catalyst variation. The high yielding, divergent reactions all proceed by an initial dearomatising spirocyclisation reaction to generate an intermediate vinyl–metal species, which then rearranges selectively by careful choice of catalyst and reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 61 publications
(19 reference statements)
2
60
0
Order By: Relevance
“…The follow-up studies from the same group 50 identified that utilizing chiral bisphosphine (R)-xylylBINAP or (S)-DTBM-SEGPHOS as the ligand could realize the highly enantioselective version of these two reactions. 51 Cu-catalyzed asymmetric propargylic substitution reaction has seen significant progress in recent years. 52 However, the scope of the carbon nucleophiles compatible with this reaction is still limited.…”
Section: Cada Reactions Involving Propargylic or Allenylic Reagentsmentioning
confidence: 99%
“…The follow-up studies from the same group 50 identified that utilizing chiral bisphosphine (R)-xylylBINAP or (S)-DTBM-SEGPHOS as the ligand could realize the highly enantioselective version of these two reactions. 51 Cu-catalyzed asymmetric propargylic substitution reaction has seen significant progress in recent years. 52 However, the scope of the carbon nucleophiles compatible with this reaction is still limited.…”
Section: Cada Reactions Involving Propargylic or Allenylic Reagentsmentioning
confidence: 99%
“…This presents ar are example of ad ivergentr eaction whereby ar egiochemical difference leads to structurallyd istinct products, so avoidingc losely relatedi somers. [17]…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating structural diversity, [19] including ring diversity to any compound class is aimed to enhancei ts potentialf or functional diversity,t hat is, to provide diversely bioactive molecules that can be used as tools to pursue chemical biology or drug-discovery goals. [11] To determine the potential of these significantly complex and diverse tetracyclic benzopyrones,t he collection was evaluated in two different cell-based screenings (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[24] In parallel, the compound collection was screenedi nh uman cervical cancerH eLa cells at ac oncentration of 30 mm to determine their cytotoxicity,i nfluence on cytoskeleton, and mitosis. [6b] Among four benzopyrones ubclasses (10,12,(15)(16)19), only 16 a-d weref ound to be cytotoxic (Table S1 and Figure S6). Regioisomeric analogues 15 did not display any influence on HeLa cells.…”
Section: Resultsmentioning
confidence: 99%